2022
DOI: 10.3389/fimmu.2022.794217
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Sarcoid-Like Reactions and Tertiary Lymphoid Structures Following Dual Checkpoint Inhibition in a Patient with Early-Stage Lung Adenocarcinoma

Abstract: Immune checkpoint inhibitor-induced sarcoid-like reactions and tertiary lymphoid structures (TLSs) are increasingly recognized but rarely reported in the same patient. We report a patient with lung adenocarcinoma who displayed sarcoid-like reactions in intrathoracic lymph nodes and tertiary lymphoid structures in surgical tumor after neoadjuvant therapy with nivolumab plus ipilimumab. Pathological examination revealed 50% residual tumor cells after treatment, and the CT evaluation of the primary tumor showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…Zhao et al. observed up-regulated PD-1 expression in peripheral blood from patients with kidney cancer ( 38 ). Hence, LAG-3 and PD-1 may serve as biomarkers for assessing disease severity and predicting prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al. observed up-regulated PD-1 expression in peripheral blood from patients with kidney cancer ( 38 ). Hence, LAG-3 and PD-1 may serve as biomarkers for assessing disease severity and predicting prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, coexpression of LAG-3 and PD-1 in peripheral blood T cells from patients with lung cancer are reported to be biomarkers for T cell dysfunction (37). Zhao et al observed up-regulated PD-1 expression in peripheral blood from patients with kidney cancer (38). Hence, LAG-3 and PD-1 may serve as biomarkers for assessing disease severity and predicting prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have documented the association between sarcoid reactions and various types of malignant tumors. The factors that cause malignancies to elicit sarcoid reactions are not clearly understood; however, many cases involve therapeutic agents, including immunosuppressive drugs [ 7 9 , 23 , 24 ]. Therefore, we summarized the reports of sarcoid reactions with a history of surgery over the past decade, including information regarding adjuvant drug use (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only one case of drug-induced sarcoid reaction could be diagnosed as sarcoid reaction by radiological findings after the drug was withheld [ 24 ]. Most sarcoid reactions are discovered at the time of primary tumor resection [ 5 , 6 , 8 , 9 , 13 , 16 , 18 , 20 22 , 26 , 27 , 29 , 30 ]; however, some (both drug-induced and non-drug-induced sarcoid reactions) are discovered 1 month to 5 years after surgery [ 10 , 14 , 15 , 17 , 19 , 23 , 25 , 28 , 31 ]. Granuloma formation is often found in lymph nodes, whereas spleen sarcoid reactions are more frequently found with non-drug-induced sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation